Site-Dependent Lineage Preference of Adipose Stem Cells - Wang, Tingliang; Hill, Ryan C.; Dzieciatkowska, Monika; Zhu, Lian; Infante, Aniello M.; Hu, Gangqing; Hansen, Kirk C.; Pei, Ming (Frontiers in Cell and Developmental Biology, 2020)
Adult stem cells have unique properties in both proliferation and differentiation preference. However, the molecular mechanisms remain unclear. In this study, we hypothesized that the matrix microenvironment plays a critical role in the fate determination of local stem cells. Four rabbits were used to provide donor-matched adipose stem cells from either subcutaneous adipose tissue (ScAT) or infrapatellar fat pad (IPFP). Proliferation and multi-lineage differentiation were evaluated in adipose stem cells from donor-matched ScAT and IPFP. RNA sequencing (RNA-seq) and proteomics were conducted to uncover potential molecular mechanisms underlying the interaction between adipose stem cells and the local matrix microenvironment. We found that stem cells from ScAT exhibited significantly higher proliferation and adipogenic capacity compared to those from donor-matched IPFP while stem cells from IPFP displayed significantly higher chondrogenic potential compared to those from donor-matched ScAT. Our findings are strongly endorsed by supportive data from transcriptome and proteomics analyses, indicating that a unique extracellular matrix microenvironment is critical in the determination of local stem cell fate.